Concrete composition and concrete coating material containing bacterium having carbon dioxide adsorption mechanism, and shotcrete construction method using the same
A concrete composition and coating material using a cementitious binder and alkaliphilic bacteria with a glycocalyx mechanism address durability and carbon dioxide absorption issues, enhancing concrete structures' durability and carbon dioxide adsorption capacity.
Patent Information
- Application Number
- JP2023163054
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-09
- Filing Date
- 2023-09-26
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-09-26
AI Technical Summary
Existing concrete structures face durability issues due to carbonation reactions with carbon dioxide, which reduce strength and promote reinforcing steel corrosion, and existing carbon dioxide adsorption methods using photocatalysts are prone to surface damage and have short service lives.
A concrete composition and coating material incorporating a cementitious inorganic binder, aggregate mixture with porous materials impregnated with alkaliphilic bacteria that form a glycocalyx, and a carbon dioxide adsorption mechanism, allowing for carbon dioxide absorption regardless of light conditions.
The composition and coating material enhance concrete durability by maintaining carbon dioxide absorption capacity even after surface damage, with a carbon dioxide adsorption rate 3 to 4 times higher than traditional methods, and can be applied to both new and existing structures.
Smart Images

Figure 2024177017000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a concrete composition and a concrete coating material that adsorb carbon dioxide, and a shotcrete construction method using the same, and more particularly to a concrete composition and a concrete coating material that have a carbon dioxide adsorption mechanism and contain bacteria that form glycocalyx, and that adsorb carbon dioxide in the atmosphere, and a shotcrete construction method using the same. [Background technology]
[0002] As damage caused by climate change increases, interest in reducing carbon dioxide, which causes climate change, is growing. Therefore, various efforts are being made across various industries to reduce carbon dioxide emissions. In particular, cement, which is necessary to manufacture concrete in the construction industry, is known to emit more than 0.8 tons of carbon dioxide for every ton produced. Therefore, the construction industry is making efforts to achieve carbon neutrality, which means that net emissions of carbon dioxide are zero for every carbon dioxide emitted.
[0003] In general cement, a carbonation reaction occurs in which calcium hydroxide (Ca(OH)2), a hydration product, reacts with carbon dioxide (CO2) to produce calcium carbonate (CaCO3), which allows the production of concrete that absorbs carbon dioxide from the atmosphere. However, this carbonation reaction changes the pH of the cement to neutral, reducing the strength of concrete structures and becoming the main cause of rebar corrosion, resulting in a significant decrease in the durability of concrete structures.
[0004] In addition, concrete that absorbs carbon dioxide from the atmosphere can be manufactured using γ-C2S contained in slag, an industrial product generated during the manufacture of stainless steel. However, this also induces carbonation of cement and can reduce the durability of concrete structures. In addition, the amount of γ-C2S generated during the manufacture of stainless steel is significantly small, making it somewhat difficult to apply this technology to industrial sites.
[0005] As a result, there is growing interest in developing technology that maintains the durability of concrete structures and adsorbs carbon dioxide from the atmosphere. For example, when a surface of a concrete structure is coated with a photocatalyst, the durability of the concrete structure can be maintained and carbon dioxide from the atmosphere can be adsorbed. However, a concrete structure coated with a photocatalyst can adsorb carbon dioxide in a strong ultraviolet environment, and when the surface coated with the photocatalyst is exposed to the outside, the coating surface can fall off or be easily damaged, resulting in a short service life.
[0006] Therefore, it is necessary to develop technology that can maintain the durability of concrete structures and adsorb carbon dioxide from the atmosphere even in environments without strong ultraviolet rays. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Registration No. 10-1877317 (2018.07.05.) Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, an object of the present invention is to provide a concrete composition and a concrete coating material that can improve the durability of a concrete structure and adsorb carbon dioxide in the atmosphere regardless of light and dark conditions. [Means for solving the problem]
[0009] In order to achieve the above object, the concrete composition according to the present invention comprises: a cementitious inorganic binder comprising at least one of ordinary Portland cement, blast furnace slag, and fly ash; and an aggregate mixture comprising a general aggregate and a porous material impregnated with alkaliphilic bacteria having a carbon dioxide adsorption mechanism and capable of forming a glycocalyx.
[0010] The cement-based inorganic binder may comprise 20 to 25 wt % of the cement-based inorganic binder and 75 to 80 wt % of the aggregate mixture.
[0011] The aggregate mixture may contain 70 to 95 vol % of the general aggregate and 5 to 30 vol % of the porous material.
[0012] The bacteria may be one or more selected from the group consisting of Rhodobacter capsulatus, Rhodopseudomonas palustris, Rhodobacter blasticus, and Rhodobacter sphaeroids.
[0013] The bacteria may be one or more selected from the group consisting of Thermoproteus, Sulfolobus, Planctomyces, and Anammox.
[0014] The porous material may include at least one of expanded vermiculite, perlite, diatomaceous earth, and superabsorbent polymer.
[0015] The porous material may be impregnated with the bacteria under negative pressure conditions.
[0016] The concrete coating material according to the present invention includes: a cementitious inorganic binder including one type of ordinary Portland cement, fly ash, blast furnace slag, and polymer powder; an aggregate mixture including fine aggregate and a porous material impregnated with alkaliphilic bacteria that have a carbon dioxide adsorption mechanism and form a glycocalyx; and a fibrous material including at least one of polyethylene and nylon.
[0017] The composition may contain 20 to 50 wt % of the cementitious inorganic binder and 50 to 80 wt % of the aggregate mixture, and may contain 0.1 to 1 part by volume of the fiber material per 100 parts by volume of the cementitious inorganic binder and the aggregate mixture.
[0018] The cement-based inorganic binder may contain 30 to 40 wt % of the one type of ordinary Portland cement, 15 to 25 wt % of the fly ash, 40 to 50 wt % of the blast furnace slag, and 1 to 10 wt % of the polymer powder.
[0019] The polymer powder may be an ethylene vinyl acetate (EVA) resin.
[0020] The aggregate mixture may contain 30 to 80 vol % of the fine aggregate and 20 to 70 vol % of the porous material.
[0021] The fiber material may have a diameter of 100 to 140 μm.
[0022] The shotcrete construction method according to the present invention uses any one of the above concrete coating materials. Effect of the Invention
[0023] The concrete composition and concrete coating material according to the present invention have a carbon dioxide adsorption mechanism, contain bacteria that form glycocalyx, improve the durability of concrete structures, and can adsorb carbon dioxide from the atmosphere regardless of light and dark conditions.
[0024] In addition, the concrete composition and concrete coating material according to the present invention have a carbon dioxide adsorption mechanism and contain alkaliphilic bacteria that form glycocalyx, and therefore even if the surface of a concrete structure is damaged, the carbon dioxide adsorption ability can be maintained by the bacteria present inside.
[0025] The concrete compositions and concrete coating materials of the present invention contain a porous material impregnated with bacteria, and can create an environment in which bacteria can grow even within the hardened concrete.
[0026] The concrete coating material according to the present invention can be easily applied to not only newly constructed concrete structures but also existing concrete structures, and can be cast onto the surface of a concrete structure that is in contact with the atmosphere to increase the efficiency of carbon dioxide absorption. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a diagram showing the mechanism by which the bacterium according to the present invention adsorbs carbon dioxide via the Calvin cycle. [Diagram 2] FIG. 2 is a diagram showing the mechanism by which the bacterium according to the present invention adsorbs carbon dioxide via the reverse TCA cycle. [Diagram 3] FIG. 3 is a diagram showing the mechanism by which the bacterium according to the present invention adsorbs carbon dioxide via the hydroxypropionate cycle. [Figure 4] FIG. 4 is a graph showing the carbon dioxide adsorption performance of the concrete blocks according to the comparative example and the experimental example at 14 days of age. [Diagram 5] FIG. 5 is a graph showing the number of surviving bacteria in the concrete blocks of the comparative example and the experimental example at 14 days of age. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Please note that in the following description, only the parts necessary for understanding the embodiments of the present invention will be described, and descriptions of other parts will be omitted to the extent that they do not deviate from the gist of the present invention.
[0029] The terms and words used in the following specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted according to the meaning and concept that corresponds to the technical idea of the present invention in accordance with the principle that the inventor can appropriately define the concept of the term in order to describe his / her invention in the best possible way. Therefore, the embodiment described in this specification and the configuration shown in the drawings are only the most preferred embodiment of the present invention and do not represent the entire technical idea of the present invention, so it should be understood that there are various equivalents and modifications that can replace them at the time of this application.
[0030] Hereinafter, embodiments of the present invention will be described in more detail with reference to the accompanying drawings. The concrete composition according to the present invention comprises a cementitious inorganic binder and an aggregate mixture.
[0031] The cementitious inorganic binder may include at least one of ordinary Portland cement, blast furnace slag, and fly ash, and the aggregate mixture may include a general aggregate and a porous material impregnated with alkaliphilic bacteria that have a carbon dioxide adsorption mechanism and form a glycocalyx.
[0032] The constitution of the concrete composition according to the present invention will be described in more detail below. The cementitious inorganic binder may consist of only ordinary Portland cement, but by replacing part of the ordinary Portland cement with blast furnace slag and fly ash, the carbon dioxide emitted during the production process of ordinary Portland cement can be reduced.
[0033] Blast furnace slag is an industrial product that is generated when pig iron is produced in blast furnaces at steelworks, and it has the effect of reducing heat of hydration and also has latent hydraulic properties that improve the long-term strength of concrete structures. Although blast furnace slag itself does not have a strong hardening property, it has the property of accelerating hardening due to the action of calcium hydroxide and sulfates, which are products of cement hydration.
[0034] Fly ash is a fine powder that dissolves with hot combustion gas when coal-based pulverized coal is burned at high temperatures in thermal power plants, and is collected by an electric or mechanical current collector in the form of spherical particles due to surface tension as it cools rapidly on its way to the chimney. Adding fly ash to a concrete composition increases the curing time somewhat, but it has the advantages of increasing the long-term strength of concrete structures, reducing heat of hydration, inhibiting alkali-aggregate reaction, improving resistance to sulfates, and improving watertightness.
[0035] The aggregate mixture may contain 70-95 vol% general aggregate and 5-30 vol% porous material.
[0036] The general aggregate may include coarse aggregate and fine aggregate, where the coarse aggregate is an aggregate that remains on a 5 mm sieve at a weight ratio of 90% or more, and preferably gravel, and the fine aggregate is an aggregate that passes through a 10 mm sieve entirely and passes through a 5 mm sieve at a weight ratio of 90% or more, and preferably sand.
[0037] The porous material may include at least one of expanded vermiculite, perlite, diatomaceous earth, and a highly absorbent resin, which have excellent cation exchange capacity. In this case, the porous material may be impregnated with alkaliphilic bacteria that have a carbon dioxide adsorption mechanism and form glycocalyx.
[0038] If bacteria are simply added during the production of concrete compositions, the bacteria are likely to die due to friction and impact during the mixing process of the concrete composition. In addition, after mixing of the concrete composition, the water content decreases due to hydration during the hardening process, creating a dry environment, and the nutrients and habitats of the bacteria decrease due to the effect of volume expansion. Furthermore, the size of the internal voids of the hardened concrete composition is 1 μm, which is smaller than the size of general bacteria, making it difficult for bacteria to survive in the concrete voids. As a result, the growth activity of bacteria is inhibited inside the hardened concrete composition, and after about 30 days, most of the bacteria are dead.
[0039] Thus, the concrete composition according to the present invention includes a porous material impregnated with bacteria, which provides an environment for the growth of bacteria within the hardened concrete composition.
[0040] The porous material may preferably have an available moisture content of 40 vol% or more and a porosity of 50 vol% or more, which can create an environment in which bacteria can grow. In particular, the porous material is preferably a material that can be used to effectively exchange exchangeable cations (Mg 2+ , Ca 2+ ) and is able to absorb bacteria and the culture fluid necessary for bacterial growth.
[0041] Generally, in concrete compositions, strong alkaline calcium hydroxide (Ca(OH)2) is produced during the hydration process, creating a strong alkaline environment of pH 11 to 12, making it difficult for sufficient light and air to reach the inside of the hardened concrete composition. Therefore, in the present invention, it is important to select alkaliphilic bacteria that are not sensitive to anaerobic, aerobic, and light / dark conditions and have a carbon dioxide adsorption mechanism.
[0042] Furthermore, the bacteria according to the present invention may be alkaliphilic bacteria that not only have a carbon dioxide adsorption mechanism but also form glycocalyx. Glycocalyx is a membrane that is formed around the bacteria due to the metabolic activity of the bacteria, and it densifies the internal structure of the concrete structure and reduces the water permeability of the concrete structure. Therefore, glycocalyx can prevent carbonation and freeze-thawing of the concrete structure, inhibit the intrusion of harmful substances such as sulfates, prevent deterioration of the concrete structure, and improve salt damage resistance.
[0043] The bacteria according to the present invention can be classified according to the carbon dioxide adsorption mechanism into bacteria having the Calvin Cycle, the Reverse Tricarboxylic Acid Cycle, and the Hydroxypropionate Cycle as the carbon dioxide adsorption mechanism.
[0044] First, the bacteria having the Calvin cycle as a carbon dioxide adsorption mechanism may include one or more species selected from the group consisting of Rhodobacter capsulatus, Rhodopseudomonas palustris, Rhodobacter blasticus, and Rhodobacter sphaeroids, which are found in purple non-sulfur photosynthetic bacteria.
[0045] Secondly, the bacteria having the reverse TCA cycle as a carbon dioxide adsorption mechanism may include one or more species selected from the group consisting of Thermoproteus and Sulfolobus.
[0046] Thirdly, the bacteria having the hydroxypropionate cycle as a carbon dioxide adsorption mechanism may be green non-sulfur bacteria, and may preferably include one or more species selected from the group consisting of Planctomyces and Anammox.
[0047] The carbon dioxide adsorption mechanism of the bacteria according to the present invention will now be described in more detail. FIG. 1 is a diagram showing the mechanism by which the bacterium according to the present invention adsorbs carbon dioxide via the Calvin cycle. Referring to FIG. 1, the Calvin cycle absorbs six molecules of carbon dioxide in the process of synthesizing glucose from ATP and NADPH. The Calvin cycle can be broadly divided into three steps. The first step is the carbon dioxide fixation step, which is catalyzed by an enzyme called rubisco. Rubisco combines ribulose-1,5-bisphosphate (RuBP), which consists of five carbons, with carbon dioxide to generate two molecules of 3-phosphoglycerate (3PG). The second step is the process in which 3-phosphoglycerate (3PG) is converted to glyceraldehyde-3-phosphate (G3P) through a reduction process. The glyceraldehyde-3-phosphate (G3P) thus generated is used to synthesize glucose. The third step is the reaction in which ribulose-1,5-bisphosphate (RuBP) is regenerated. In the second step, glyceraldehyde-3-phosphate (G3P) produced is converted to ribulose-1,5-bisphosphate (RuBP) via ribulose monophosphate (RuMP). The regenerated ribulose-1,5-bisphosphate (RuBP) can then bind to carbon dioxide and adsorb it.
[0048] FIG. 2 is a diagram showing the mechanism by which the bacterium according to the present invention adsorbs carbon dioxide via the reverse TCA cycle. Referring to Figure 2, the reverse TCA cycle reverses the TCA cycle and adsorbs three carbon dioxide molecules in the process of converting carbon dioxide into acetyl-CoA. The reverse TCA cycle uses enzymes such as fumarate reductase, which reduces fumarate to succinate, α-ketoglutarate:ferredoxin oxidoreductase, which transfers electrons received as ferredoxin to carbon dioxide and succinyl-CoA and reduces them to α-ketoglutarate, and ATP citrate lyase, which breaks down citrate to produce oxaloacetate and acetyl-CoA.
[0049] FIG. 3 is a diagram showing the mechanism by which the bacterium according to the present invention adsorbs carbon dioxide via the hydroxypropionate cycle. Referring to FIG. 3, the hydroxypropionate cycle adsorbs two carbon dioxide molecules during the process of converting acetyl-CoA to malyl-CoA. The specific steps of the hydroxypropionate cycle in adsorbing carbon dioxide are as follows: first, acetyl-CoA adsorbs carbon dioxide to form malonyl-CoA, which is converted to propionyl-CoA via the intermediate hydroxypropionate. Next, propionyl-CoA adsorbs carbon dioxide during the process of carboxylation to methylmalonyl-CoA, which is isomerized to succinyl-CoA. Then, succinyl-CoA forms malyl-CoA, which is decomposed into acetyl-CoA and glyoxylate.
[0050] The 3-hydroxypropionate / 4-hydroxybutyrate cycle and the dicarboxylate / 4-hydroxybutyrate cycle are known as carbon dioxide adsorption mechanisms that are modifications of the hydroxypropionate cycle.
[0051] The concrete composition according to the present invention has a carbon dioxide adsorption mechanism, contains alkalophilic bacteria that form glycocalyx, improves the durability of concrete structures, and can adsorb carbon dioxide from the atmosphere regardless of light and dark conditions.
[0052] In addition, the concrete composition according to the present invention has a carbon dioxide adsorption mechanism and contains alkaliphilic bacteria that form glycocalyx. Even if the surface of the concrete structure is damaged, the bacteria present inside can maintain the carbon dioxide adsorption ability, and the concrete composition can exhibit a carbon dioxide adsorption rate that is 3 to 4 times higher than the carbon dioxide adsorption rate due to carbonation of general concrete.
[0053] The porous material can be sterilized using nanobubble water, then completely immersed in a culture solution in which bacteria have been cultured at a weight ratio of 1:3-4, and then impregnated with bacteria by applying negative pressure. The process of applying negative pressure here can be performed in a negative pressure container at 15-25°C and 1-30 torr for 20-80 minutes, but is not limited thereto.
[0054] Nanobubble water, which is used to sterilize porous materials, is made of ultrafine water droplets containing oxygen, and the bubbles contain a large amount of oxygen. Therefore, when a porous material is washed with nanobubble water, the amount of dissolved oxygen inside the porous material is increased, and the activity of photosynthetic bacteria can be increased. Nanobubble water can also remove foreign matter attached to the surface of the porous material, and since the hydroxyl radicals generated in the water have a (-) property, they can adsorb to (+) ions, which are pollutants, and remove the pollutants. When nanobubbles are generated in nanobubble water, oxygen in the air is activated to form molecules such as ozone (O3) and hydroxyl groups (-OH), which can act as disinfectants that destroy organisms and volatile organic compounds. In this case, the porous material can be washed with nanobubble water and then dried at 100°C for 6 to 10 hours, but is not limited thereto.
[0055] In order to ensure that the concrete composition according to the present invention has a favorable carbon dioxide adsorption rate, the bacteria are cultured at 1 × 10 in an incubator at 5 to 50 ° C. 9 The culture medium may be cultured at a concentration of 100000000000 cells / mL or more, and may contain, but is not limited to, yeast extract, disodium succinate hexahydrate, and potassium dihydrogen phosphate (KH2PO4). For example, the culture medium may contain, per liter of purified water, 1.0 g / L yeast extract, 1.0 g / L disodium succinate hexahydrate, 0.5 mL / L ethanol, 1 mL / L Ferric citrate solution (0.5%), 0.5 g / L potassium dihydrogen phosphate (KH2PO4), 0.4 g / L magnesium sulfate (MgSO4·7H2O), 0.4 g / L sodium chloride (NaCl), 0.4 g / L ammonium chloride (NH4Cl), 0.05 g / L calcium chloride (CaCl2·2H2O), and 1 mL / L trace element solution (SL-6).
[0056] The concrete composition according to the present invention may contain 20-25wt% of cementitious inorganic binder and 75-80wt% of aggregate mixture, or preferably 23wt% of cementitious inorganic binder and 77wt% of aggregate mixture. In this case, the ratio of water-binder may be 30-50%. The method for producing the concrete composition is according to a commonly known method, and therefore the description thereof will be omitted.
[0057] The concrete coating material according to the present invention comprises a cementitious inorganic binder, an aggregate mixture, and a fibrous material.
[0058] The cementitious inorganic binder may include one type of ordinary Portland cement, fly ash, blast furnace slag, and polymer powder, the aggregate mixture may include fine aggregate and a porous material impregnated with alkaliphilic bacteria having a carbon dioxide adsorption mechanism and forming a glycocalyx, and the fibrous material may include at least one of polyethylene and nylon.
[0059] The structure of the concrete coating material according to the present invention will be described in more detail below. The cementitious inorganic binder may be composed of only one type of ordinary Portland cement, but by replacing a part of the one type of ordinary Portland cement with blast furnace slag and fly ash, it is possible to reduce the carbon dioxide emitted during the production process of the one type of ordinary Portland cement. For example, the cementitious inorganic binder may contain 30-40 wt% of one type of ordinary Portland cement, 15-25 wt% of fly ash, 40-50 wt% of blast furnace slag, and 1-10 wt% of polymer powder.
[0060] Here, the polymer powder can improve adhesion to concrete structures, and ethylene vinyl acetate (EVA) resin can be used.
[0061] The aggregate mixture may include 30-80 vol% fine aggregate and 20-70 vol% porous material, where the fine aggregate is an aggregate having a diameter of 5 mm or less, and may include sand, bottom ash, and crushed stone.
[0062] The porous material contained in the concrete coating material according to the present invention is the same as the porous material impregnated with alkaliphilic bacteria having a carbon dioxide adsorption mechanism and forming glycocalyx contained in the concrete composition according to the present invention, and therefore a description thereof will be omitted.
[0063] The fiber material prevents deformation such as expansion and contraction of the concrete coating material, and may include at least one of polyethylene and nylon fibers. In this case, the fiber material may have a diameter of 100 to 140 μm, preferably 120 μm.
[0064] The concrete coating material according to the present invention may contain 20-50 wt% of a cementitious inorganic binder and 50-80 wt% of an aggregate mixture, or may contain 0.1-1 volume part of a fiber material per 100 volume parts of the cementitious inorganic binder and aggregate mixture. In this case, the water-binder ratio may be 20-50%.
[0065] The concrete coating material according to the present invention can be applied by a shotcrete application method in which compressed air is used to spray the material through a hose and cast onto the surface of a concrete structure. Shotcrete application can penetrate even very small gaps on the surface of a concrete structure, ensure adhesion, and increase the density and strength of the concrete structure. For example, the concrete coating material according to the present invention can be compressed and sprayed using a mobile mixer with a capacity of 10 to 60 L, a mono pump with a pumping force of 300 to 1000 rpm and 40 to 100 bar, and an air compressor of 100 to 1000 kPa, and cast once or twice.
[0066] The concrete coating material according to the present invention can be easily applied to not only newly constructed concrete structures but also existing concrete structures, and can be cast onto the surface of a concrete structure that is in contact with the atmosphere to increase the efficiency of carbon dioxide absorption.
[0067] [Comparative Examples and Experimental Examples] In order to confirm the carbon dioxide adsorption performance of the concrete composition according to the present invention, concrete blocks according to comparative examples and experimental examples were manufactured.
[0068] Comparative Example 1 has a water-cement ratio of 40%, cement of 23 wt%, and fine aggregate of 77 wt%, and a unit cement amount of 450 kg / m 3 The concrete block is made of crushed fine aggregate.
[0069] In Experimental Example 1, the water-cement ratio was 40%, cement was 23 wt%, and aggregate mixture was 77 wt%, and the unit cement amount was 450 kg / m 3 The aggregate mixture is a concrete block containing 90 vol% fine aggregate and 10 vol% porous material. The porous material used was made by immersing expanded vermiculite in a culture solution in which Rhodobacter capsulatus was cultured in a negative pressure container, and then applying a pressure of 10 to 30 torr for 30 minutes to impregnate the bacteria.
[0070] Example 2 was identical to Example 1, except that the aggregate mixture was a concrete block containing 80 vol. % fine aggregate and 20 vol. % porous material.
[0071] Example 3 was identical to Example 1, except that the aggregate mixture was a concrete block containing 70 vol. % fine aggregate and 30 vol. % porous material.
[0072] Example 4 was identical to Example 1, except that the aggregate mixture was a concrete block containing 60 vol.% fine aggregate and 40 vol.% porous material.
[0073] Example 5 was identical to Example 1, except that the aggregate mixture was a concrete block containing 50 vol.% fine aggregate and 50 vol.% porous material.
[0074] The mixing ratio of the bacteria-impregnated porous material in the aggregate mixture in Comparative Example 1 and Experimental Examples 1 to 5 is shown in Table 1 below.
[0075] [Table 1]
[0076] Comparative Example 1 and Experimental Examples 1 to 5 were placed in a sealed container saturated with 3000 ppm of carbon dioxide, and the carbon dioxide concentration inside the sealed container was confirmed after 14 days of use.
[0077] FIG. 4 is a graph showing the carbon dioxide adsorption performance of the concrete blocks according to the comparative example and the experimental example at 14 days of age. 4, carbon dioxide of 100 ppm or less was detected in the sealed container in which the concrete blocks of Experimental Examples 2 to 5, in which the bacteria-impregnated porous material had a mixing rate of 20 vol% or more, were inserted at 14 days old. In other words, it was confirmed that the concrete blocks of Experimental Examples 2 to 5, in which the bacteria-impregnated porous material had a mixing rate of 20 vol% or more, showed a carbon dioxide adsorption rate of about 96.7% or more.
[0078] FIG. 5 is a graph showing the number of surviving bacteria in the concrete blocks of the comparative example and the experimental example at 14 days of age. Referring to FIG. 5, the concrete blocks of Experimental Examples 2 to 5, in which the bacteria-impregnated porous material had a mixing ratio of 20 vol% or more, had a 1.0×10 4 It was confirmed that the number of viable bacteria was more than 100 cells / mL.
[0079] In addition, in order to confirm the durability depending on the mixing ratio of the bacteria-impregnated porous material in the concrete composition according to the present invention, the compressive strength and flexural strength of Comparative Example 1 and Experimental Examples 1 to 5 at an age of 28 days were measured and are shown in Table 2 below.
[0080] [Table 2]
[0081] Referring to Table 2, it was confirmed that the concrete blocks of Comparative Example 1, in which the bacteria-impregnated porous material was mixed in at 50 vol% or less, and Experimental Examples 1 to 5, had a compressive strength of 20 MPa or more at 28 days, and the concrete blocks of Comparative Example 1, in which the bacteria-impregnated porous material was mixed in at 40 vol% or less, and Experimental Examples 1 to 5, had a flexural strength of 5 MPa or more at 28 days.
[0082] In addition, the embodiments disclosed in this specification and the drawings are merely specific examples presented to aid in understanding, and are not intended to limit the scope of the present invention. It is obvious to a person having ordinary skill in the art to which the present invention pertains that other modifications based on the technical idea of the present invention can be implemented in addition to the embodiments disclosed herein.
Claims
1. a cementitious inorganic binder comprising at least one of ordinary Portland cement, blast furnace slag, and fly ash; an aggregate mixture including a general aggregate and a porous material impregnated with alkaliphilic bacteria having a carbon dioxide adsorption mechanism and forming a glycocalyx; 1. A concrete composition comprising:
2. 2. The concrete composition of claim 1, comprising 20-25 wt. % of said cementitious inorganic binder and 75-80 wt. % of said aggregate mixture.
3. 3. The concrete composition of claim 2, wherein the aggregate mixture comprises 70-95 vol. % of the general aggregate and 5-30 vol. % of the porous material.
4. 2. The concrete composition of claim 1, wherein the bacteria is one or more selected from the group consisting of Rhodobacter capsulatus, Rhodopseudomonas palustris, Rhodobacter blasticus, and Rhodobacter sphaeroides.
5. 2. The concrete composition of claim 1, wherein the bacteria is at least one selected from the group consisting of Thermoproteus, Sulfolobus, Planctomyces, and Anammox.
6. 10. The concrete composition of claim 1, wherein the porous material comprises at least one of expanded vermiculite, perlite, diatomaceous earth, and a superabsorbent resin.
7. 2. The concrete composition of claim 1, wherein the porous material is impregnated with the bacteria under negative pressure conditions.
8. a cementitious inorganic binder comprising one ordinary Portland cement, fly ash, blast furnace slag, and polymer powder; an aggregate mixture including fine aggregate and a porous material impregnated with alkaliphilic bacteria having a carbon dioxide adsorption mechanism and forming a glycocalyx; A fiber material including at least one of polyethylene and nylon; 2. A concrete coating material comprising:
9. The cement-based inorganic binder comprises 20 to 50 wt % and an aggregate mixture comprises 50 to 80 wt %; 9. The concrete coating material according to claim 8, wherein the fiber material is contained in an amount of 0.1 to 1 part by volume per 100 parts by volume of the mixture of the cement-based inorganic binder and aggregate.
10. The concrete coating material according to claim 9, characterized in that the cement-based inorganic binder comprises 30-40 wt% of the one kind of ordinary Portland cement, 15-25 wt% of the fly ash, 40-50 wt% of the blast furnace slag, and 1-10 wt% of the polymer powder.
11. 9. The concrete coating material according to claim 8, wherein the polymer powder is an ethylene vinyl acetate (EVA) resin.
12. 10. The concrete coating material according to claim 9, wherein the aggregate mixture contains 30 to 80 vol % of the fine aggregate and 20 to 70 vol % of the porous material.
13. 9. The concrete coating material according to claim 8, wherein the fiber material has a diameter of 100 to 140 μm.
14. A shotcrete construction method using the concrete coating material according to any one of claims 8 to 13.
Citation Information
Patent Citations
Method for manufacturing bacterial slime-based coating materials using porous materials to immobilize bacterial agents and near-neutral binders
CN108947380B
Synthetic fibers and cementitious tissue containing them
JP2002541048A
Cement-based materials and repair agents for structures, and methods for preparing them.
JP2011509915A
Pavement concrete and manufacturing method for the same
JP2014025323A
Concrete protective coating material
JP2018104608A
